PERSEPSI DAN ASPIRASI MASYARAKAT TERHADAP PENGEMBANGAN KAWASAN MINAPOLITAN BUNTOK SEBERANG KECAMATAN DUSUN SELATAN KABUPATEN BARITO SELATAN PROVINSI KALIMANTAN TENGAH - Leliana Leliana; Idiannor Mahyudin; Suhaili Asmawi; Mahrus Aryadi (EnviroScienteae, 2013)
This research aims to 1) know the public perception of the development area minapolitan Buntok Seberang, 2) explore the factors that influence people's perception of regional development minapolitan Buntok Seberang such as education, employment, income, length of residence, counseling, and the death of goldfish; 3) explore the community's aspirations for regional development activities minapolitan Buntok Seberang. This research uses survey methods, focused on the heads of households (families) who has cages (karamba)  in Barito River, where the carp are maintained by experienced mass death, are 4 (four) villages/rural, that is Hilir Sper, Buntok Kota, Baru and Teluk Telaga which is part of the plan minapolitan. Proportionate number of respondents who were sampled as many as 65 the heads of households with 37 families in the data distribution of Hilir Sper, 19 households in the Buntok Kota, 6 families in Baru and 3 households in Teluk Telaga. The results showed that the public perception of the development of the region is positive minapolitan Buntok Seberang or beneficial to society. People's perceptions are influenced by factors of education, employment, income, length of residence / attempt and death of a goldfish. Aspirations of the people against the development of the area minapolitan Buntok Seberang the need for help production facilities (saprodi) fishery, handling marketing, capital assistance, guidance / counseling on a regular basis as well as the support from the local fishery cooperatives / agencies.